B- and T-cell acute lymphoblastic leukemias evade chemotherapy at distinct sites in the bone marrow - Barz, Malwine J.; Behrmann, Lena; Capron, Danaëlle; Zuchtriegel, Gabriele; Steffen, Fabio D.; Kunz, Leo; Zhang, Yang; Vermeerbergen, Iria Jimenez; Marovca, Blerim; Kirschmann, Moritz; Zech, Antonia; Nombela-Arrieta, César; et al. (Haematologica (Roma), 2023)
Persistence of residual disease after induction chemotherapy is a strong predictor of relapse in acute lymphoblastic leukemia (ALL). The bone marrow microenvironment may support escape from treatment. Using three-dimensional fluorescence imaging of ten primary ALL xenografts we identified sites of predilection in the bone marrow for resistance to induction with dexamethasone, vincristine and doxorubicin. We detected B-cell precursor ALL cells predominantly in the perisinusoidal space at early engraftment and after chemotherapy. The spatial distribution of T-ALL cells was more widespread with contacts to endosteum, nestin+ pericytes and sinusoids. Dispersion of T-ALL cells in the bone marrow increased under chemotherapeutic pressure. A subset of slowly dividing ALL cells was transiently detected upon shortterm chemotherapy, but not at residual disease after chemotherapy, challenging the notion that ALL cells escape treatment by direct induction of a dormant state in the niche. These lineage-dependent differences point to niche interactions that may be more specifically exploitable to improve treatment.